2013
DOI: 10.4103/0976-3147.112752
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of cerebral palsy on families: The African perspective

Abstract: Background:Psychological stress associated with cerebral palsy (CP) is known to be one of the most depressing conditions of families. In the traditional African society, some peculiar factors may contribute to the stress.Aims:The aims of this study were to identify and describe, from the African perspective, the psychological impact of CP on families and determine the strategies adopted by families in coping with it.Settings and Design:The study was a cross-sectional descriptive survey conducted in the Physiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 14 publications
3
34
1
3
Order By: Relevance
“…In Denham, Adongo, Freydberg, and Hodgson's (2010) mixed methods study, participants (community and family members, health nurses, and spiritualists) in Northern Ghana consistently identified children with disability as "spirit children," which they defined as "bush spirits born into a family in human forms so that they can access the good things and destroy them" (p.611). These traditional and uninformed views of CP are reflected in the findings of other studies (Gona et al, 2010;McNally & Mannan, 2013;Olawale, Deih, & Yaadar, 2013). The prevalence of these misconceptions in rural settings in African countries is alarming, as they have negative implications for the caregiving process and decrease the efficacy of rehabilitation programmes when these are available (Nyante et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…In Denham, Adongo, Freydberg, and Hodgson's (2010) mixed methods study, participants (community and family members, health nurses, and spiritualists) in Northern Ghana consistently identified children with disability as "spirit children," which they defined as "bush spirits born into a family in human forms so that they can access the good things and destroy them" (p.611). These traditional and uninformed views of CP are reflected in the findings of other studies (Gona et al, 2010;McNally & Mannan, 2013;Olawale, Deih, & Yaadar, 2013). The prevalence of these misconceptions in rural settings in African countries is alarming, as they have negative implications for the caregiving process and decrease the efficacy of rehabilitation programmes when these are available (Nyante et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…terutama biaya perawatan anak (Olawale, 2013). Beban finansial tersebut akan berdampak pada respon psikologis dari pengasuh.…”
Section: Pendahuluanunclassified
“…In a cross-sectional descriptive survey conducted in the Physiotherapy Department of a tertiary hospital in Nigeria, the authors found that personal problems that were experienced by parents of children with cerebral palsy included loss of job, lack of concentration at work, loss of family joy as well as derangement of financial affairs of the family. They however concluded that families caring Texila International Journal of Public Health Volume 6, Issue 1, Feb 2018 for children with cerebral palsy generally had a positive attitude towards their children despite the challenges [15]. Till date, there is paucity of data on health promotion and stress management intervention for parents of cerebral palsy children in African countries especially, in Nigeria.…”
Section: Introductionmentioning
confidence: 99%